Сontrolling parameters determining technological properties of a helicon discharge system - Semenyuk, V.F.; Virko, V.F.; Korotash, I.V.; Osipov, L.S.; Polotsky, D.Yu.; Rudenko, E.M.; Slobodyan, V.M.; Shamrai, K.P. (Вопросы атомной науки и техники, 2013)
In experiments on two helicon sources driven by a planar antenna, it is shown that the plasma density in the drift chamber and the energies and density of the ion flux onto the substrate holder can be effectively controlled by changing the local magnetic field and the holder potential. Експериментами на двох геліконних джерелах з плоскою збуджуючою антеною показано, что густиною плазми в дрейфовій камері та енергіями і густиною іонного потоку на підкладинкотримач можна ефективно керувати зміненням локального магнітного поля і потенциалу тримача. Экспериментами на двух геликонных источниках с плоской возбуждающей антенной показано, что плотностью плазмы в дрейфовой камере и энергиями и плотностью ионного потока на подложкодержатель можно эффективно управлять изменением локального магнитного поля и потенциала держателя.